2020
DOI: 10.1021/acsami.0c07745
|View full text |Cite
|
Sign up to set email alerts
|

General Aggregation-Induced Emission Probes for Amyloid Inhibitors with Dual Inhibition Capacity against Amyloid β-Protein and α-Synuclein

Abstract: Amyloid self-assembly is pathologically linked to many neurodegenerative diseases, including Alzheimer’s disease (AD) and Parkinson’s disease (PD). While many inhibitors have been developed individually for specific amyloid proteins, there are a few effective platforms to screen on a large scale general amyloid inhibitors against different amyloid proteins. Herein, we developed a new class of amyloid inhibitor probes by site-specific conjugation of aggregation-induced emission (AIE) molecules with amyloid prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 67 publications
3
32
0
Order By: Relevance
“…Meanwhile, researchers have also made many efforts to develop amyloid aggregation inhibitors in order to promote the therapy of AD. They have discovered kinds of Aβ aggregation-regulated molecules and nanomaterials by exploring the interaction between amyloid and antibodies 33 - 38 , peptides 39 - 44 , small molecules 45 - 51 , aptamers 52 - 56 , polymers 57 - 59 , as well as nanomaterials 60 - 63 . Most of these inhibitors can regulate the aggregation process of Aβ in vitro or in vivo and reduce the cytotoxicity caused by Aβ aggregates to a certain extent, providing a valuable treatment strategy for delaying AD progression.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, researchers have also made many efforts to develop amyloid aggregation inhibitors in order to promote the therapy of AD. They have discovered kinds of Aβ aggregation-regulated molecules and nanomaterials by exploring the interaction between amyloid and antibodies 33 - 38 , peptides 39 - 44 , small molecules 45 - 51 , aptamers 52 - 56 , polymers 57 - 59 , as well as nanomaterials 60 - 63 . Most of these inhibitors can regulate the aggregation process of Aβ in vitro or in vivo and reduce the cytotoxicity caused by Aβ aggregates to a certain extent, providing a valuable treatment strategy for delaying AD progression.…”
Section: Introductionmentioning
confidence: 99%
“…25 So far, several studies associated with AIE have been reported on the detection of amyloid fibrils including insulin, Ab 42 and lysozyme. 17,[26][27][28][29][30][31][32][33][34][35][36] Due to their highly emissive properties in supramolecular assembly and the supramolecular assembly of amyloid monomers into fibrils, these kinds of probes are quite suitable for fibril detection. However, there were a few fluorescent probes that can monitor the content of fibril aggregates and also had inhibition effects on protein amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of A β inhibitors including biomolecules [ [23] , [24] , [25] , [26] ], functionalized nanomaterials and nanoparticles [ 16 , 17 , [27] , [28] , [29] , [30] , [31] ], have been shown to decelerate the aggregation of A β and suppress cellular toxicity of amyloid. For example, Sun et al.…”
Section: Introductionmentioning
confidence: 99%